محمد خيضر ودوره النضالي الوطني 1936-1967 - براهيمي, العرافي (University of Eloued جامعة الوادي, 2021)
تتمحور هذه الدراسة التاريخية حول الدور النضالي لشخصية محمد خيضر الذي دافع عن القضية الوطنية وتصدى للاستعمار الفرنسي، بفضل نشاطه السياسي منذ انضمامه لحزب نجم شمال أفريقيا خلال سنة 1936م إلى غاية بداية الاستقلال، حيث تمكن بالرغم من مستواه التعليمي والثقافي المتواضع، من تقلد عدة مسؤوليات في صفوف حزب الشعب الجزائري، حتى أصبح ممثلا له في البرلمان الفرنسي مدافعا عن حقوق الشعب الجزائري، وأظهر منذ البداية انتماءه للتيار الثوري من خلال دعمه للمنظمة الخاصة، والمشاركة الى جانب قيادتها في الهجوم على بريد وهران سنة1949، حتى تضمن استمرارية نشاطها بهدف التحضير لتفجير الثورة التحريرية. هذا الهدف الذي تجسد سنة 1954، وشارك في التحضير لهذا الهدف هذه المرة خارج الوطن بصفته المسؤول الأول عن الوفد الخارجي لجبهة التحرير الوطني بالقاهرة. فبرز كدبلوماسي ومفاوض محنك على المستوى الدولى. وفي بداية الاستقلال وبعد خروجه من السجن كان من أبرز الشخصيات التي ساهمت في إعادة بناء الدولة الجزائرية، وتجاوز محنة أزمة صيف1962، وأثبت بأنه أهل لتحمل أخطر وأكبر المهام على مستوى أعلى هرم السلطة، وعين كأول أمين عام لحزب جبهة التحرير الوطني. لقد اختار شعار بناء دولة مستقلة يتمتع فيها الجميع بالحرية، ويتم بناءها على أسس ديمقراطية، غير أنه دفع ثمن هذا الاختيار في نهاية المطاف، بعد تصفيته واغتياله بالعاصمة الاسبانية مدريد سنة 1967م، حتى لا يتحول إلى زعيم سياسي يقود المعارضة بالخارج في عهد الرئيس هواري بومدين، وخاصة انه كان باستطاعته التحكم في الودائع المالية الخاصة بجبهة التحرير الوطني بالخارج. وهكذا انتهت مسيرة رجل دولة قدم ما عليه من تضحيات لشعبه ولوطنه في الداخل وفي الخارج. This historical study deals with the role of the militant Mohamed Khider who stands against French Colonisation thanks to his politcal work since he catches up with the star of north Africa party in 1936 AC till the begining of the independence. Athough his modest cultural and learning level, He occupies several post in the aforesaid party untill he becomes a representative in French Parliament defending the Algerian people Rigths he shows, at first, his belonging to revolutionary trend through his support to the Special Organisation O.S and he takes part in the attack on the Oran post- office in 1949 to insure her activity continuity in order to prepare for the outbreak of the liberation war in 1954, so he becomes the first responsible to the foreign delegation of the national liberation front in Cairo. Mohamed khider becomes one of the most outstanding personalities after his release from jail in the begining of the independence ; so he plays an important role in rebuilding Algeria and he gets through summer issue 1962 the thing which leads him to assume greater responsiblities ; first of all he appointed as a General Secretary of the National Liberation Front Party and he chooses as motto an independent nation where every one can enjoy freedom and democracy. because of that he was assassinated in Spain -Madrid -in 1967 to put an end to his opposition abroad during Hawari Boumedien reign especially as he was able to control national liberation front deposits abroad . That was the end of a great Man who devoted himself to his people and nation to be kept safe and sound .
أطروحة دكتوراه في التاريخ تخصص تاريخ حديث ومعاصر
Keywords: محمد خيضر، الوفد الخارجي، حزب الشعب الجزائري، الثورة التحريرية، جبهة التحرير الوطني، الاستقلال.; : Mohamed Khider, the foreign delegation, the Algerian People's Party, the Liberation Revolution, the National Liberation Front, the Independence.